Política social de acolhimento social: a percepção dos moradores de rua sobre os serviços prestados pelo albergue municipal de Santana do Livramento - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This study aims to evaluate the perception of homeless individuals regarding the services provided by the Municipal Shelter in Santana do Livramento, focusing on the role of social assistance in promoting their inclusion and reintegration. The theoretical framework is grounded in the concepts of public policy, social inclusion, and street-level bureaucracy. The research uses a qualitative and quantitative approach, combining document analysis and field interviews. Data were collected through questionnaires administered to both shelter users and the shelter director to assess service satisfaction and primary needs.The results indicate that, while users view the shelter as essential support during moments of extreme vulnerability, there are limitations regarding the support provided for social reintegration and the occupational opportunities offered. The shelter director highlighted management challenges, such as resource scarcity and the need for flexibility to address high demand, which requires adaptations in service delivery. The study concludes that the shelter plays a critical role in assistance but requires improvements to broaden its role in social reintegration, facilitating user access to conditions that promote autonomy and help them overcome vulnerability.
Social policy of shelter: the perception of homeless individuals regarding the services provided by the municipal shelter of Santana do Livramento
Keywords: Políticas públicas; Burocratas de nível de rua; Inclusão social; Public policies; Street-level bureaucrats; Social inclusion; CNPQ::CIENCIAS SOCIAIS APLICADAS